An Interview with the Abnormally Normal Robert Falls - Garvey, Sheila (The Eugene O Neill Review, 2026)
Keywords: EPIC; Long day; Performance art; Poetry; dept.thr

Irish repertory theatre: celebrating thirty-five years off-Broadway - Garvey, Sheila (The Eugene O Neill Review, 2026)
Keywords: Celtic languages; Diaspora; Immigration; Irish; Period (music); dept.thr

(Connecticut Historic Theatres) - Peterson, Thom (1991)
Keywords: dept.thr; faculty_collection; sabbatical_report

Eleonora Duse: A Biography - Sheehy, Helen (Alfred A. Knopf, 2003)
Keywords: Biography; Duse; Eleonora; 1858-1924; Actors; Italy; dept.thr; faculty_collection

Jason Robards Remembered: Essays and Recollections - Black, Stephen A; Brietzke, Zander; Bryer, Jaskson R.; Garvey, Shelia Hickey (McFarland & Co., 2002)
Keywords: Anecdotes; Interviews; Robards; Jason; Robards; Jason; dept.thr; faculty_collection

Book Review: Ah, Wilderness! - Garvey, Sheila Hickey (The Eugene O'Neill Review, 2022)
Connecticut’s Tony Award–winning Hartford Stage reopening with Eugene O’Neill’s only comedy, Ah, Wilderness!, was a historic event. It marked Melia Bensussen’s debut as a director at Hartford Stage. Bensussen had already been in place as its first woman artistic director in October 2019, but began her tenure overseeing other directors’ work. The theater’s forced closing in March 2020 due to the COVID-19 pandemic delayed her joining the theater’s directing pool. Ah, Wilderness! had already been cast and was ready to begin rehearsals when the shutdown occurred.The fall 2021 opening for Bensussen’s directorial debut might have been guided by fate, as October 16 is Eugene O’Neill’s birthday. O’Neill had a fascination with fate and destiny stemming from his deep and tangled roots in Connecticut. Ah, Wilderness! is the comedic and fantastical version of the playwright’s youthful days in the Nutmeg State, while Long Day’s Journey Into Night is the tragic and more accurate version. What unites the two plays is that they both take place in the waterfront Monte Cristo Cottage, a historic landmark in New London.The choice to reopen Hartford Stage with Ah, Wilderness! was also historic because to attend the performance one had to present proof of a COVID vaccination or a recent negative test and wear protective facial masking—something that became a common practice nationally and internationally when COVID protocols were established. Once cleared, the audience was permitted to enter the auditorium, where they were treated to a more recognizable theatrical experience. Visible on the theater’s spacious thrust stage were portions of an abstract set designed by James Noone, hidden, for the most part, behind a white sheet-like curtain. On the stage’s foreground were furnishings draped with individual sheets. The abandoned and ghostly look was ably enhanced by lighting designer Wen-Ling Liao’s stark lighting, which signaled a death or an abandonment on the stage and in the entire theater facility itself.Also symbolic was the initial music selected to mark Hartford Stage’s reawakening. As the house lights were raised, individual singers could be heard repeatedly singing, two words and notes, a cappella. The words were “I am.” The unique arresting declaration was quickly followed by the proud entrance of the remaining cast and some crewmembers, joyfully marching though the auditorium. They headed toward the stage’s thrust, also singing “I am” until they all broke into a full rendition of the famous Americana song “Yankee Doodle Dandy” —an apt choice, the play occurs on the Fourth of July. But the melody and words “I am” signified even more because the music and lyrics were written by the iconic stage Irishman George M. Cohan, who portrayed Nat Miller in the original production of Ah, Wilderness!, which premiered on Broadway on October 2, 1933.As the actors entered, the white drop curtain rose to reveal a super-size—and not entirely historically accurate—skeletal set that served as a universal environment. Its main purpose was to represent the Miller family home, and its secondary purpose was to eventually represent the act 4, scene 2 lakeside woods where Richard Miller, the play’s central young lead (Michael Boatman), and his teenage love interest, Muriel McComber (Brittany Anikka Liu), meet under full moonlight to confess their undying love. The cast continued singing while they removed the white coverings from the furniture. Their actions were a reminder that the Monte Cristo Cottage was the O’Neill family’s summer home. In this way, the Miller family’s initial actions echoed the O’Neills’ annual return. Once the 1906 period furniture pieces were fully visible and lit with warm stage lighting, the delightful summertime period costumes designed by Olivera Gajic could be appreciated in their proper context.Throughout the production’s exposition and early conflicts, the audience was introduced to an American family and a New London community compatible with racial norms of the twenty-first century. Unlike the original Broadway production and many productions since, the cast was multiracial, an appropriate reflection of contemporary times. As Nat Miller, Boatman maintained a demeanor of gentle but firm moral force when addressing challenges to his integrity as a newspaper editor, familial rebellions against his patriarchal authority, and the antics of the none-too-skilled maid, Norah (Annie Jean Buckley). As the play unfolds, it becomes apparent that Nat and his devoted wife Essie (Antoinette LaVecchia) are raising four children: Arthur (Antonio Jose Jeffries), Richard (Jaevon Williams), Tommy (Miles Lowe), and Mildred (Katerina McCrimmon). Nat has also assumed the responsibility of caring for several relatives including his single sister, Lily (Natascia Diaz), and his wife’s hopelessly alcoholic brother, Sid Davis (McCaleb Burnett). Boatman wisely and lovingly guided his family and his rebellious teenage son, Richard, with a loving, measured pace. The actor shouldered his character’s purpose, leading to the climactic moments when O’Neill’s goal becomes apparent. As a playwright aiming to bring classical stature to American playwrighting, O’Neill intended to write a comedy of substance. He did not want to write his only comedy by ending it with a happy and sentimental resolution. Instead, O’Neill concludes Ah, Wilderness! with philosophical reflections on the importance of familial loyalty and everlasting love.A clear choice of director Bensussen was to craft her production as an ensemble piece rather than as a star vehicle for a leading role, as it has often been: Cohan (1933), Jason Robards (1988), Geraldine Fitzgerald (1969 and 1973), and Colleen Dewhurst (1988). As a result, there were numerous memorable performances by actors with secondary speaking roles: Tanner Jones as Wint Selby, Stuart Rider as the protective Bartender, Joseph Adams as Macomber and the Salesman, and Liu, doubling as Belle, all made brief but standout appearances at unexpected moments. Diaz in the principal role of spinster Lily Miller imbued her character with a poignant dignity, a feat made more impressive by the fact that, in some productions, this character can arc toward the melodramatic and comically belittling.An informative post-show talk-back took place on November 6, with Bensussen, Beth Wynstra, and Steven Bloom, the latter two representing the Eugene O’Neill Society’s board of directors. During the conversation, Bensussen noted pitfalls she found in the writing of Miller family matriarch Essie Miller and acknowledged cutting some of the character’s dialogue to make her seem less scatterbrained. The result was a less dominant but more mature rendering of the character.In choosing to direct Ah, Wilderness!, Bensussen demonstrated her prowess as a stage director and her appreciation for the home-grown legacy of America’s only Nobel Prize–winning playwright. She also lovingly reawakened the dormant Hartford Stage.
0 citations (Crossref) [2023-10-31]
Keywords: dept.thr

Father-daughter lust: Psychiatric aspects of abusive incest - Marvasti, J.A.; Dripchak, V.L. (American Journal of Forensic Psychiatry, 2006)
Sexual violation of children has been a long standing problem that has a wide range of impact upon the victim, her/his family, the community where the family lives and our society as a whole. Traumatic incest, in particular, is an abuse of power, a challenge to the child's sense of trust in people and a thief of childhood. This article will explore the intricate issues surrounding the incest relationship between fathers and their child daughters and provide a discussion of current therapeutic interventions. Copyright 2006 American Journal of Forensic Psychiatry.
Keywords: behavior therapy; child sexual abuse; cognitive therapy; daughter; dept.swk; father child relation; human; incest; play therapy; review; sexual behavior; sexual crime; trust; ⛔ No DOI found

The origins of the O'Neill renaissance: A history of the 1956 productions of the iceman cometh and long day's journey into night - Garvey, Sheila Hickey (Theatre Survey, 1988)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/022-731-490-947-472 tex.type: [object Object]
Keywords: dept.thr